2021
DOI: 10.3390/jmse9070767
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Reinforcement Learning to Predict Shaft Deformation Considering Hull Deformation of Medium-Sized Oil/Chemical Tanker

Abstract: The enlargement of ships has increased the relative hull deformation owing to draft changes. Moreover, design changes such as an increased propeller diameter and pitch changes have occurred to compensate for the reduction in the engine revolution and consequent ship speed. In terms of propulsion shaft alignment, as the load of the stern tube support bearing increases, an uneven load distribution occurs between the shaft support bearings, leading to stern accidents. To prevent such accidents and to ensure shaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(40 reference statements)
3
4
0
Order By: Relevance
“…Which is in agreement with the results obtained from dimensional analysis found also in literature for cantilever beam, but similarity cannot be ensured at a mixed type of beam including both a cantilever and a simply supported beam, since the similarity parameters in Equations ( 7)-( 9) are not the same as the ones demanded in Equations ( 12)- (14). Therefore, a supplementary phase is required, to couple this theoretical background with the complexity of the application for marine shafting systems.…”
Section: Quantitysupporting
confidence: 90%
See 1 more Smart Citation
“…Which is in agreement with the results obtained from dimensional analysis found also in literature for cantilever beam, but similarity cannot be ensured at a mixed type of beam including both a cantilever and a simply supported beam, since the similarity parameters in Equations ( 7)-( 9) are not the same as the ones demanded in Equations ( 12)- (14). Therefore, a supplementary phase is required, to couple this theoretical background with the complexity of the application for marine shafting systems.…”
Section: Quantitysupporting
confidence: 90%
“…In that particular case study of the shafting system of an 82,000 DWT bulk carrier, the initial alignment of the vessel was compared against the performance corresponding to different bearing offset combinations. Similar studies have been recently reported by other researchers especially focusing on the important effect of hull structural deformations in regard to shaft alignment [12][13][14]. These studies collectively tackle various interconnected issues pertinent to marine shafting system operations, with a shared focal point: shaft deflection.…”
Section: Introduction and Literature Trendssupporting
confidence: 60%
“…In that particular case study of the shafting system of an 82000 DWT bulk carrier, the initial alignment of the vessel was compared against the performance corresponding to different bearing offset combinations. Similar studies have been recently reported by other researchers especially focusing in the important effect of hull structural deformations in regard to shaft alignment [12][13][14].…”
Section: Introduction and Literature Trendssupporting
confidence: 88%
“…Bearing failure will cause increased shaft vibration, reduced propulsion efficiency, and oil leakage. Reports of bearing failures have shown an increasing trend in recent years with the extending size of ships [1]. For example, three patrol vessels of the Indian Coast Guard experienced bearing wear failures [2], 11 of 17 identical commercial ships were subjected to bearing incidents [3], and DNV GL Classification has noted that they have received increasing reports of aft propeller shaft bearing damage in recent years [4].…”
Section: Introductionmentioning
confidence: 99%